Analisis dan Uji Korelasi Tingkat Kebisingan Lalu Lintas: Ruas Jalan Bundaran Waru Kota Surabaya - Mohammad Maghfur Ali; Dian Majid (JITEKH, 2023)
Abstractâˆ’This study aims to analyze noise levels and provide recommendations for noise control. Noise tests were conducted using a sound level meter, in accordance with the SNI 8427-2017 standard, at three sampling points. Data analysis covered vehicle volume (in emp), average noise levels (Ls), correlation tests, and control recommendations. Data processing was carried out using Microsoft Excel, SPSS (25), and Sketchup software. The results showed that the highest vehicle volume reached 2,090 vehicles per hour with a composition percentage of motorcycles (MC) at 69.3%, light vehicles (LV) at 56.2%, and heavy vehicles (HV) at 9.4%, in line with the emp values of MKJI (1997). The noise level (Ls) reached a fairly high level, hitting 72.5 dB. There is a moderate to very strong relationship between vehicle volume and noise levels (with correlation values ranging from 0.450 to 0.874). To control the noise, it is suggested to add vegetation barriers such as Acacia trees and Sebe shrubs, which can enhance the effectiveness of existing barriers in reducing noise to below the quality standard as per the Minister of Environment Regulation No. 48 of 1996 for residential and commercial areas